The Koinōnia of Non-Being and Logos in the Sophist Account of Falsehood - Wiitala, Michael (2022)
At Sophist 260e3-261a2, the Eleatic Stranger claims that in order to demonstrate that falsehood is, he and Theaetetus must first track down what speech (logos), opinion (doxa), and appearance (phantasia) are, and then observe the communion (koinōnia) that speech, opinion, and appearance have with non-being. The Stranger, however, never explicitly discusses the communion of speech, opinion, and appearance with non-being. Yet presumably their communion is implicit in his account of falsehood, given his claim that observing that communion is needed in order to demonstrate that falsehood is (260e5-a2). This essay seeks to make the communion that speech has with non-being explicit. I argue that speech has communion with non-being in that the things and actions speech combines together by means of nouns and verbs need not be combined in a way that reveals (δηλοῖ) how the being a given speech is about combines ontologically with other beings.